Cellulose fiber reinforced polyvinyl alcohol composite material
The isotropic composite materials prepared by reacting with cellulose solve the problem of decomposition of highly hydrolyzed polyvinyl alcohol before melting point, and achieves its thermal processing and performance improvement, which is suitable for the manufacturing of multifunctional packaging materials and engineering components.
Patent Information
- Application Number
- CN202380062789.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-31
- Filing Date
- 2023-08-30
- Publication Date
- 2025-04-11
AI Technical Summary
The highly hydrolyzed polyvinyl alcohol decomposes before the melting point reaches, resulting in difficulty in melting processing, and its mechanical and chemical properties are poor, making it difficult to process in existing devices.
Isotropic composite materials are prepared by reacting with cellulose materials, and the thermal application process is used to form a stable composite structure with cellulose, thereby improving its processability and performance.
It realizes thermal processing of high hydrolytic polyvinyl alcohol, improves the tensile strength, flexibility and thermal stability of composite materials, reduces brittleness, and is suitable for the manufacture of multifunctional packaging materials and engineering components.
Smart Images

Figure BDA0005290130180000071 
Figure BDA0005290130180000081 
Figure BDA0005290130180000082
Abstract
Description
[0001] The present invention relates to a composite material comprising polyvinyl alcohol and cellulose-based fibers, the manufacture of the composite material and a product comprising or including the composite material.
[0002] Polyvinyl alcohol is usually prepared by hydrolysis of polyvinyl acetate. Polyvinyl alcohol made by partial or complete hydrolysis of homopolyvinyl acetate is called homopolyvinyl alcohol. The degree of hydrolysis determines the properties of the resulting polymer. Copolyvinyl alcohol or homopolyvinyl alcohol with a low degree (LD) of hydrolysis is easy to process, but has poor mechanical and chemical properties. Homopolyvinyl alcohol with a high degree (HD) of hydrolysis, for example, a degree of hydrolysis of 85% or more, has excellent properties, but it is not processable without degradation under conditions using equipment used to make other polymers such as polyolefins. The present invention particularly relates to polyvinyl alcohol prepared by hydrolysis of homopolyvinyl acetate.
[0003] Like many carbohydrates, highly hydrolyzed polyvinyl alcohol, i.e., with a degree of hydrolysis greater than 70%, decomposes before reaching its melting point of about 250°C. This makes melt processing difficult. For this reason, highly hydrolyzed polymers are usually processed into aqueous solutions. Partially hydrolyzed polyvinyl alcohol is more easily melt processed.
[0004] Due to the difference in chain structure, a significant difference between highly hydrolyzed (high degree of hydrolysis, HD) polyvinyl alcohol and partially hydrolyzed (low degree of hydrolysis, LD) polyvinyl alcohol is the degree and quality of crystalline order. Polyvinyl alcohol with less than 2% unhydrolyzed acetate groups can easily crystallize to form strongly hydrogen-bonded crystalline domains. These crystalline domains have essentially the same structure as that found in polyethylene. This may be attributed to the small size of the hydroxyl groups. However, due to hydrogen bonding, the melting point of highly hydrolyzed polyvinyl alcohol is about 150°C higher than that of polyethylene.
[0005] Polyols have been used as plasticizers, but efficient production of plasticized polyvinyl alcohol with a high degree of hydrolysis has been difficult to achieve.
[0006] WO2017 / 046361 discloses a method for producing plasticized polyvinyl alcohol having a degree of hydrolysis of 98 wt % or more.
[0007] According to a first aspect of the present invention, a method for manufacturing a composite material comprises the following steps:
[0008] Providing a mixture of polyvinyl alcohol and fibrous or non-fibrous cellulosic material;
[0009] heating the mixture to a temperature of 190° C. or higher;
[0010] allowing the mixture to react to form a composite mixture; and
[0011] The mixture is allowed to cool to form an isotropic solid composite material.
[0012] According to a second aspect of the invention, a composite material comprises an isotropic reaction product of polyvinyl alcohol and a fibrous or non-fibrous cellulosic material,
[0013] The amount of the cellulosic material is in the range of about 0.1 wt % to about 50 wt % of the total weight of the composition.
[0014] The polyvinyl alcohol may be a homopolymeric polyvinyl alcohol.
[0015] The composite material can be distinguished from a simple mixture or blend in which the polyvinyl alcohol and cellulose components are substantially unchanged. In an embodiment, after the reaction with the polyvinyl alcohol, it is no longer possible to observe cellulose fibers or non-fibrous cellulose particles, thereby obtaining an isotropic composite material.
[0016] A homogeneous composite material can be obtained, in which individual domains comprising cellulose are no longer present. The structure of the composite material can be determined using scanning electron microscopy.
[0017] The cellulosic material comprises fibrous cellulose or non-fibrous cellulose, such as granular cellulose or powdered cellulose.
[0018] The cellulosic material may be selected from the group consisting of cellulose pulp, unbleached cellulose pulp, enzyme treated cellulose pulp, chemically treated cellulose pulp, microfibrillated and nanofibrillated cellulose, modified cellulose including methyl cellulose, hydroxypropyl cellulose, ethyl cellulose and mixtures thereof.
[0019] Cellulose esters, such as cellulose acetate, are not used.
[0020] Composite materials can exhibit a range of advantageous properties that cannot be achieved using unreacted solutions of the two components.
[0021] Composite materials can be made by controlled application of heat to a mixture of polyvinyl alcohol and cellulosic material. For this purpose, the polyvinyl alcohol must be heat processable under the conditions required to react with the cellulose.
[0022] A minimum temperature in the range of 190°C to 240°C may be employed, for example in the range of 205°C to 215°C.
[0023] The reaction is preferably carried out in the absence of any solvent.
[0024] The reaction may be carried out by passing the mixture through an extruder maintained at a temperature of 190° C. to 240° C. A fixed rotor speed may be employed.
[0025] The polyvinyl alcohol may be: a polyvinyl alcohol composition comprising a homopolymeric polyvinyl alcohol having a degree of hydrolysis of 65 wt % to 98 wt % or more and a molecular weight ranging from 4,000 to 20,000;
[0026] A plasticizer selected from the group consisting of diglycerol, triglycerol, fructose, ribose, xylose, D-mannitol, triacetin, pentaerythritol, dipentaerythritol, methylpentanediol, 1,2-propylene glycol, 1,4-butylene glycol, 2-hydroxy-1,3-propylene glycol, 3-methyl-1,3-butylene glycol, 3,3-dimethyl-1,2-butylene glycol, polyethylene glycol 300, polyethylene glycol 400, alkoxylated polyethylene glycol, caprolactam, tricyclic trimethylolpropaneformal, rosin ester, erucamide, and mixtures thereof; and
[0027] An optional stabilizer selected from the group consisting of sodium stearate, potassium oleate, sodium benzoate, calcium stearate, dimethyl propionic acid, and mixtures thereof.
[0028] The degree of hydrolysis may be from 65 to 98 wt%, such as from 67 to 85 wt%, alternatively from 86 to 93 wt%, such as from 94 to 98 wt%.
[0029] The polyvinyl alcohol composition may have a melt flow index (MFI) of 5 to 50 g / 10 min, such as 10 to 35 g / 10 min, such as 10 to 15 g / 10 min. The melt flow index mentioned in this specification is measured by conventional techniques using a 10 kg weight at 230°C.
[0030] The molecular weight of the polyvinyl alcohol may range from 4,000 to 20,000, such as 4,000 to 15,000, for example 4,000 to 9,000, alternatively 12,000 to 20,000. The molecular weights referred to in this specification are weight average molecular weights and may be measured using conventional liquid chromatography techniques.
[0031] The polyvinyl alcohol composition is preferably stable at the temperatures at which it is melted and extruded. Polyvinyl alcohol without plasticizers and stabilizers as disclosed herein, especially homopolymers with a high degree of hydrolysis, tend to decompose at the temperatures required to react with cellulose, such as by melt and extrusion processing.
[0032] The stable polyvinyl alcohol polymer used in the present invention can be prepared using the methods disclosed in WO2022 / 008516 and WO2022 / 008521, the disclosures of which are incorporated herein by reference for all purposes.
[0033] The polyvinyl alcohol composition can be prepared by a method comprising the following steps:
[0034] introducing a polyvinyl alcohol polymer comprising a homopolymeric polyvinyl alcohol or a blend thereof having a degree of hydrolysis ranging from 65 wt % to 98 wt % or more into a mixing reactor;
[0035] wherein the mixing reactor comprises a blending chamber having a main inlet, a main outlet and at least two intermeshing components extending between the main inlet and the main outlet, the components being arranged to apply shear forces to the polymer while the components transport the polymer from the inlet through the reaction zone to the outlet;
[0036] one or more secondary inlets, the one or more secondary inlets being located downstream of the primary inlet for introducing reactants including a processing aid, a plasticizer, and a reactive stabilizer into the chamber to form a reaction mixture;
[0037] wherein the plasticizer is selected from the group disclosed above;
[0038] wherein when the reactive stabilizer is present, the reactive stabilizer is selected from the group consisting of sodium stearate, potassium oleate, sodium benzoate, calcium stearate, dimethyl propionic acid, and mixtures thereof;
[0039] wherein the blending chamber comprises a plurality of heating zones arranged such that the mixture is subjected to a temperature profile whereby the temperature increases from the inlet to the outlet;
[0040] a secondary outlet located between the reaction zone and the primary outlet, the secondary outlet being arranged to allow removal of a processing agent from the chamber;
[0041] reacting a processing aid, a plasticizer, and a polymer in a reaction zone to form a plasticized polymer; and
[0042] The plasticized polymer is allowed to pass through the main outlet.
[0043] Using a reactive mixing device according to the present invention, typically an extruder, allows processing aids and plasticizers to react with polyvinyl alcohol or its blend without decomposing the polymer, and then removes all or most of the processing aids from the secondary outlet to obtain plasticized polyvinyl alcohol or its blend. This provides a polyvinyl alcohol composition suitable for reacting with the cellulosic material according to the present invention.
[0044] The use of reactive stabilizers can advantageously reduce the degree of degradation during melt processing to form the composite materials of the present invention. This allows homopolymeric polyvinyl alcohols having a high degree of hydrolysis, such as 88 wt% or more, to be processed to form fibers, pellets or other forms suitable for reaction with cellulose.
[0045] The reactive stabilizer may be used in an amount of about 0.1 wt % to about 5 wt %, such as about 0.1 wt % to about 3 wt %, such as 0.1 wt % to about 1.5 wt %, such as about 0.2 wt % to about 0.5 wt %, such as about 0.25 wt %.
[0046] The reactive stabilizers of the present invention can reduce the degree of degradation of the polymer during processing. Homopolymer polyvinyl alcohol is difficult to process because it degrades at the high temperatures required. The tendency to degrade leads to the use of polyvinyl alcohol copolymers, resulting in a loss of engineering properties. The degree of degradation can be determined by UV spectroscopy analysis of the amount of conjugate present in the polymer. Sodium benzoate has been found to be particularly effective.
[0047] The use of homopolyvinyl alcohol is particularly advantageous. Homopolyvinyl alcohol is produced by the hydrolysis of homopolyvinyl acetate, in embodiments of the invention the degree of hydrolysis being 65 wt % or more. For example, polyvinyl alcohol copolymers prepared by the hydrolysis of polyvinyl acetate copolymers disclosed in US 2005 / 001348 (Kohnen) have inferior properties compared to homopolyvinyl alcohol. The composite material formed according to the invention from homopolyvinyl alcohol and cellulose can exhibit advantageous properties, such as high tensile strength and flexibility.
[0048] Polyvinyl alcohol can be produced by hydrolyzing homopolymeric polyvinyl acetate, wherein the degree of hydrolysis is in the range of 65 to 98 wt %, such as 67 to 85 wt %, such as 86 to 93 wt %, such as 94 to 98 wt %.
[0049] A blend of two or more polyvinyl alcohol polymers may be employed, for example a blend of two polyvinyl alcohol polymers having a relatively high molecular weight and a relatively low molecular weight, respectively.
[0050] Blends of polyvinyl alcohols having the same molecular weight and different degrees of hydrolysis can be combined. Blending different grades of polyvinyl alcohol together enables the properties of the resulting polymer to be improved, such as melt strength.
[0051] The blend of polymers of different molecular weights used is selected based on the physical properties desired in the finished product. This may require the use of materials of different molecular weights. It may be advantageous to use more than two polymers of different molecular weights. The use of a single molecular weight polymer is not excluded.
[0052] Use of blends can allow control of the viscosity of the polymer. Selection of stabilizers according to the present invention allows use of blends of desired viscosity without loss of other properties. Alternatively, use of blends can allow use of polyvinyl alcohol with one or more stabilizers while maintaining viscosity or other properties to allow manufacture of pellets or films.
[0053] The processing aid is preferably water. Alternatively, the processing aid may comprise a mixture of water and one or more hydroxy compounds having a boiling point lower than the boiling point or melting point of the plasticizer. Water is preferably used for cost and environmental reasons.
[0054] In an embodiment, the plasticizer may be selected from the group consisting of diglycerol, triglycerol, xylose, D-mannitol, triacetin, dipentaerythritol, 1,4-butanediol, 3,3-dimethyl-1,2-butanediol, and caprolactam.
[0055] Binary mixtures of plasticizers may be advantageous.
[0056] The total amount of plasticizer in the formulation may be from about 15% to about 30% by weight.
[0057] In embodiments, the cellulose may comprise unbleached pulp fibers.
[0058] The amount of unbleached pulp fibers may range from about 0.1 wt% to about 50 wt%, preferably from about 10 wt% to about 40 wt%.
[0059] In an embodiment, the cellulose may comprise enzyme-modified cellulose microfibers or nanofibers.The amount of enzyme-modified cellulose microfibers or nanofibers may range from about 0.1 wt% to about 30 wt%, preferably from about 5 wt% to 20 wt%.
[0060] According to another aspect of the present invention, there is provided a product comprising an isotropic reaction product of a heat processable homopolyvinyl alcohol having a degree of hydrolysis of 65 wt% or more and cellulose. The product may be made according to the second aspect of the present invention.
[0061] The composite materials of the present invention exhibit advantageous properties. Composite materials comprising cellulose, such as unbleached cellulose pulp fibers, and polyvinyl alcohol can be stronger and exhibit higher tensile strength and lower ductility than corresponding unfilled polyvinyl alcohol. Brittleness can be reduced. Increasing the amount of unbleached cellulose pulp fibers can increase the tensile strength and tensile modulus of the composite materials compared to the individual components and physical mixtures of the individual components, thereby allowing unexpectedly high values to be achieved.
[0062] The composite material of the present invention can be used to make heat-processable pellets, which can be processed by extrusion to form, for example, films, fibers and rigid thermoformed products, such as food trays, bottles and other containers. Unreacted cellulose products cannot be heat-processed by, for example, extrusion or film coating.
[0063] The composite material of the invention can be applied as a coating to a substrate by melt extrusion. Cellulosic substrates such as paper or board can be coated.
[0064] According to another aspect of the present invention, there is provided a thermoformable pellet consisting of or comprising a composite material according to the preceding aspect of the present invention.
[0065] Composites containing unbleached cellulose pulp fibers can change the intermolecular and intramolecular structure of polyvinyl alcohol, thereby affecting the crystallization and physical properties of the composite. Adding unbleached cellulose pulp fibers can significantly increase the glass transition temperature. Without wishing to be bound by theory, this may indicate that the fibers limit the segment mobility of the polymer chains due to the bonding interactions between the fibers and the polymer chains. Enthalpy, melting temperature and crystallization temperature can increase, indicating that the polyvinyl alcohol crystallinity increases. This may be due to the pulp fibers acting as nucleating agents for the polyvinyl alcohol, thereby increasing the crystallinity and crystallite size.
[0066] Unless otherwise stated, percentages and other amounts referred to in this specification are by weight and are selected from any ranges cited to total 100%.
[0067] The present invention is further described by way of examples, which however do not have any limiting meaning.
[0068] Example 1
[0069] The table below shows the properties of composite materials comprising polyvinyl alcohol (PVOH) and 0, 10, 20 and 30 wt% unbleached cellulose pulp fibers.
[0070] Table 1
[0071]
[0072]
[0073] Example 2
[0074] The table below shows a comparison between composite materials comprising polyvinyl alcohol (PVOH) with and without fibers, polylactic acid (PLA) with and without fibers, and polypropylene (PP) with and without cellulose fibers.
[0075] Table 2
[0076]
[0077] *Contains compatibilizer
[0078] The properties of the composites of the present invention are superior to those of polypropylene. Composites containing PLA do not show good barrier properties.
[0079] The polyvinyl alcohol used has the following properties:
[0080]
[0081] The composite materials of the present invention can be used to manufacture environmentally sustainable multifunctional packaging materials. These materials can provide favorable thermal and mechanical properties, including barrier, antimicrobial, antioxidant and UV blocking properties. Composite materials can also be used to manufacture engineering parts, such as automotive parts and aerospace parts.
[0082] Example 3
[0083] Slurry preparation
[0084] Dry cellulose pulp (92% dry solids content Nordic Paper UKP, unbleached softwood kraft pulp from Swedish pine and spruce) was comminuted by running it through a twin screw extruder at 50°C and 150 rpm. The extruder was open at the front and had screws without a mixing section. The resulting powder was a homogenous pulp powder with a dry content of 95% by weight and a degradation temperature of 250°C.
[0085] Example 4
[0086] Extrusion of polyvinyl alcohol-cellulose pulp composites
[0087] Mixtures were prepared containing a blend of polyvinyl alcohol (50 wt %) having a 98 wt % hydrolysis degree and a molecular weight of 160,000 and polyvinyl alcohol (50 wt %) having a 94 wt % hydrolysis degree and a molecular weight of 55,000 and 0 wt %, 10 wt %, 20 wt % and 30 wt % of unbleached pulp fibers.
[0088] The components were added to a feed hopper and extruded through a co-rotating twin-screw extruder Lab Tech LTE-20-48 with a screw diameter of 20 mm and a length / depth ratio of 48. The feed rate was 50 g / min. The operating speed was 200 rpm. 12 continuous heating zones were maintained at the following temperatures (° C.): 90° C., 90° C., 70° C., 190° C., 190° C., 200° C., 200° C., 210° C., 215° C., 220° C., 230° C., 230° C., 220° C., 200° C.
[0089] After leaving the die zone, the material was allowed to flow on a conveyor at 9.2 rpm and was cooled using a fan.
[0090] Example 5
[0091] Experimental study on cellulose pulp / polyvinyl alcohol composites
[0092] The pellets obtained from the previous examples were injection molded in a BOY 25E VH injection molding unit to provide samples for tensile and impact tests. The following temperature profile and 20°C mold were used for injection molding. The five heating zones were maintained at 215°C, 225°C, 225°C, 190°C and 180°C, respectively. The injection molding was set at 1200 bar and 10 cm 3 / s.
[0093] Tensile tests were performed using a procedure based on ISO 527.
[0094] Prior to testing, the samples were conditioned at 25°C in 50% humidity for at least 72 hours. Tensile modulus, strength and strain at break were measured using an MTS flexure test 60 controlled hydraulic actuator at an initial speed of 1 mm / min, which was increased to 50 mm / min after 0.5% strain. Data were collected at a rate of 500 Hz using MTS SERIES 793 controlled software.
[0095] The impact testing procedure was performed on a Zwick / Roell HIT 5P impact tester using a 5J pendulum using the Charpy notched impact test. This measures the toughness of a material under impact loading by the deformation required to break the specimen.
[0096] Differential Scanning Calorimetry (DSC) was based on ISO 11357-3:2018 procedure. DSC measurements were obtained on a Mettler-Toledo DSC822e calorimeter. The tests were performed at a flow rate of 50 mL.min -1 The samples were placed in a standard aluminum crucible (40 μL) under a nitrogen atmosphere. The thermal regime was set at 98 °C.min -1Thermogravimetric analysis (TGA) was based on the ASTM E2550 procedure. TGA measurements were obtained using a Mettler-Toledo 851 instrument. The test was performed at a flow rate of 50 mL.min -1 8 mg of each sample was placed in a ceramic cup.
[0097] From 30℃ to 400℃, the thermal scheme was set at 10℃.min -1 The results are shown in Table 3.
[0098]
[0099] Example 6
[0100] Manufacturers of Enzymatic Cellulose Nanofiber (CNF) Reinforcement Agents
[0101] Refined pulp with a pulp consistency of 4 wt% was treated with an enzyme mixture obtained from Novonzyme in a sulfate buffer solution at pH 7.2 for 2 hours at 50° C. An example of pretreated pulp with a fiber consistency of 2 wt% was homogenized using a high pressure fluidizer Microfluidiser-110EH (Microfluidics, USA) at 1700 bar through a 200 / 100 μM chamber.
[0102] The properties of the treated fibers are as follows:
[0103]
[0104]
[0105] Comparative Example 7
[0106] Composite material manufacturing
[0107] Comparative examples were carried out using dispersions at 70°C followed by film casting.
[0108] At 70°C, the polyvinyl alcohol pellets were dissolved in water under stirring to obtain a 10 wt% suspension. Under stirring at 500 rpm for 2 hours, 2 wt% of cellulose nanofibers were heated to 70°C and mixed with the polyvinyl alcohol solution to obtain composite materials with 5 wt%, 10 wt% and 20 wt% of cellulose nanofibers. The samples were sonicated using an ultraTuruz to eliminate fiber aggregation in order to provide a homogeneous dispersion. After sonication, the samples were vacuum degassed to eliminate any bubbles.
[0109] The suspension was transferred to a square Petri dish and kept at room temperature. A transparent film of 22.5 cm size was obtained with an average thickness of 431 + 51 μ and a weight of about 23 g.
[0110] The films were cut, dried and compounded in a HAAKE Mini Lab II counter-rotating twin-screw extruder at 220°C and 100 rpm to obtain pellets of composite materials.
[0111] The pellet samples were pressed to a thickness of 0.4 mm using a Servitec Polystat 200T laboratory hot press at 220°C with a force of 25 kN. The compounded samples were cut to obtain seven strips with dimensions of 45×6 mm. The samples were conditioned at 50% humidity and 23°C for at least 30 hours before testing. The tensile modulus, strength, strain at break and tensile energy absorption were measured using an MTS tensile strength machine at a speed of 3 ml / min and an initial gap between the grippers of 30 mm.
[0112] Dynamic Scanning Calorimetry (DSC) is based on ISO 11357-3:2018. Real-time DSC measurements were obtained on a Mettler-Toledo DSC 822e calorimeter. The tests were performed at a flow rate of 50 mL.min -1 The experiment was carried out under a nitrogen atmosphere. 4 mg of each sample was placed in a standard aluminum crucible (40 μL). The thermal scheme was set to 10 °C (min -1 ),as follows:
[0113] a) Heating stage from -10°C to 200°C
[0114] b) Isothermal stage at 200°C for 1 min
[0115] c) Cooling from 200℃ to -10℃
[0116] d) Isothermal stage at -10°C for 1 min
[0117] e) Heating stage from -10°C to 400°C
[0118] Thermogravimetric analysis (TGA) was performed according to ASTM E2550. TGA measurements were obtained in a Mettler-Toledo 851. The test was performed at a flow rate of 50 mL.min. -1 The experiment was carried out under a nitrogen atmosphere. 8 mg of each sample was placed in a ceramic cup. The thermal program was set to 10 °C.min -1 , from 30℃ to 400℃.
[0119] Compared with the composite material from method 1, the method of the present invention produces a composite material with improved tensile strength and tensile modulus but with reduced elongation and toughness. Compared with pure polyvinyl alcohol, the addition of enzymatic cellulose nanofibers to polyvinyl alcohol produces a stronger and more rigid composite material, but the strain and toughness are reduced. During compounding, a clear correlation between cellulose nanofiber content, tensile strength and modulus was observed. Both formulations reached the highest values in the composite material with 20% by weight cellulose nanofibers. The addition of cellulose nanofibers increased the glass transition temperature. This may indicate that the fibers limit the segment mobility of the polymer chain during the reaction. When the cellulose nanofiber content is greater than 5% by weight, the crystallinity as well as the melting temperature and crystallization temperature are reduced by extrusion compounding. This may indicate that the cellulose nanofibers hinder the crystallization of polyvinyl alcohol or cause degradation of the polymer chain. Extrusion was carried out at 220°C. The results are summarized in the following table:
[0120]
[0121]
[0122] Example 8
[0123] Additional compositions were investigated.
[0124] The polyvinyl alcohol used was partially hydrolyzed, having a low molecular weight and a degree of hydrolysis of 67% to 89%, as follows:
[0125]
[0126] The plasticizers used are listed below. Water was used as a processing aid and sodium benzoate was used as a stabilizer.
[0127]
[0128] The following formulations were prepared using various commercial cellulose products.
[0129]
[0130]
[0131]
[0132]
[0133] Cellulose Type 5 - Hydrophobically modified high aspect ratio wood fiber
[0134] Cellulose Type 6 - Soluble Modified Plant Fiber
[0135]
[0136] result
[0137] Thermal analysis including differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) was used to study the thermal stability of the composites and to observe the melting temperature and recrystallization temperature of the polymers. The crystallinity (%) was calculated and estimated by DSC.
[0138] TGA analysis of cellulose samples was performed to determine the thermal stability of pure cellulose before compounding with PVOH. Cellulose types 3 and 4 showed the highest thermal stability.
[0139] Based on DSC, TGA analysis and torque stabilizer (batch mixer), it was concluded that PVOH / cellulose was compatible for compounding and that some of these formulations were suitable for scale-up.
[0140] TGA analysis showed that after the addition of cellulose, the PVOH polymer still showed thermal stability up to at least 230°C.
[0141] DSC analysis demonstrated the thermal stability of the composites.
[0142] Changing the plasticizer from dipentaerythritol to ε-caprolactone was effective in reducing the melting peak temperature and the recrystallization temperature as shown in the table below.
[0143]
[0144]
[0145] Studies in batch mixers show that compounding proceeds smoothly. After the maximum peak, the torque reaches a constant level and there is no sign of degradation or incompatibility. In addition, by adding cellulose, the maximum torque increases, confirming that more energy is required for compounding due to the presence of cellulose. The polymers are blended at a fixed rotor speed while the torque is recorded as a function of time. The results show the thermomechanical history that the polymers undergo under mixing. When the polymers are introduced into the mixing chamber, the torque increases due to the energy required to melt and compound the polymers. The torque then decreases and reaches a steady state.
[0146] For the cellulose / PVOH composite formulation, a single peak was observed. This indicated that a single reaction occurred. No cross-linking or degradation occurred during the residence time required to process the polymers. There was no evidence of incompatibility between the polymers.
[0147] By adding cellulose, the maximum torque increases, confirming that more force and energy are required for compounding due to the presence of cellulose. It is concluded that the resulting PVOH / cellulose composite has greater strength than unreacted PVOH.
[0148] The TGA and DSC measurements show that the composite material exhibits thermal stability. The greater temperature stability at temperatures above 230°C is significant because the two separate unreacted polymers exhibit lower stability under these temperature conditions. This shows a permanent interaction between the polymers. This is confirmed by SCM analysis, which shows that there are no separate original polymer domains in the composite material. This is also shown in the crystallization differences shown by DSC analysis.
Claims
1. A method for manufacturing a composite material, the method comprising the following steps: Providing a mixture of polyvinyl alcohol and fibrous or non-fibrous cellulosic material; heating the mixture to a temperature of 190° C. or higher; allowing the mixture to react to form a composite mixture; and The mixture is allowed to cool to form an isotropic solid composite material.
2. The method of claim 1, wherein the polyvinyl alcohol is a homopolymer polyvinyl alcohol.
3. A method according to any preceding claim, wherein the cellulosic material is fibrous, granular or powdered cellulose.
4. A method according to any preceding claim, wherein the cellulosic material is selected from the group consisting of unbleached cellulose pulp, enzyme treated cellulose pulp, chemically treated cellulose pulp, microfibrillated and nanofibrillated cellulose, modified cellulose, methyl cellulose, hydroxypropyl cellulose, ethyl cellulose and mixtures thereof.
5. A process according to any preceding claim, wherein the polyvinyl alcohol has a degree of hydrolysis of 65% to 98% by weight or more.
6. The method according to claim 5, wherein the polyvinyl alcohol has a degree of hydrolysis of 67 wt% to 85 wt% or more.
7. The method of claim 5, wherein the polyvinyl alcohol has a degree of hydrolysis of 94 wt% to 98 wt% or more.
8. A method according to any preceding claim, wherein the polyvinyl alcohol comprises homopolymeric polyvinyl alcohol having a degree of hydrolysis of 70% to 98% by weight or more and a molecular weight in the range of 20,000 to 140,000; A plasticizer selected from the group consisting of diglycerol, triglycerol, fructose, ribose, xylose, D-mannitol, triacetin, pentaerythritol, dipentaerythritol, methylpentanediol, 1,2-propylene glycol, 1,4-butylene glycol, 2-hydroxy-1,3-propylene glycol, 3-methyl-1,3-butylene glycol, 3,3-dimethyl-1,2-butylene glycol, polyethylene glycol 300, polyethylene glycol 400, alkoxylated polyethylene glycol, caprolactam, tricyclotrimethylolpropane methylal, rosin ester, erucamide, and mixtures thereof; and A stabilizer selected from the group consisting of sodium stearate, potassium oleate, sodium benzoate, calcium stearate, dimethyl propionic acid, and mixtures thereof.
9. The method according to any preceding claim, wherein the polyvinyl alcohol composition has a melt flow index (MFI) in the range of 5 g / 10 min to 50 g / 10 min, preferably 10 g / 10 min to 35 g / 10 min, more preferably 10 g / 10 min to 15 g / 10 min.
10. A method according to any preceding claim, wherein the polyvinyl alcohol has a molecular weight in the range of 4,000 to 20,000.
11. A method according to any preceding claim, wherein the polyvinyl alcohol has a molecular weight in the range of 4,000 to 15,000.
12. A method according to any preceding claim, wherein the polyvinyl alcohol has a molecular weight in the range of 4,000 to 9,000.
13. A method according to any preceding claim, wherein the polyvinyl alcohol has a molecular weight in the range of 12,000 to 20,000.
14. A process according to any preceding claim, wherein the mixture is heated to a temperature in the range 190°C to 240°C.
15. A process according to any preceding claim, wherein the mixture is heated to a temperature in the range 205°C to 215°C.
16. A method according to any preceding claim, wherein the mixture is heated by passing through an extruder.
17. A composite material according to any preceding claim, wherein the cellulosic material is fibrous cellulose.
18. A method according to any preceding claim, wherein the polyvinyl alcohol is a blend of two or more homopolymeric polyvinyl alcohols.
19. A composite material comprising an isotropic reaction product of polyvinyl alcohol and a cellulosic material, the amount of the isotropic reaction product being from 0.1 wt% to 50 wt% of the total weight of the composite material.
20. A composite material comprising the isotropic reaction product of polyvinyl alcohol and a cellulosic material, said composite material being prepared by the method of any preceding claim.
21. A heat-processable pellet consisting of or comprising the composite material according to claim 20.
22. A heat processable pellet comprising the composite material of claim 21 and a filler or other additive.
23. A coated substrate, wherein the coating comprises the composite material according to claim 19 or 20.
Citation Information
Patent Citations
Plastic shaped bodies based on polyvinyl alcohol, method for the production thereof involving thermoplastic methods, and their use
US20050001348A1
Process and apparatus for manufacture of processable polyvinyl alcohol
WO2017046361A1
Method for manufacture of a plasticised polyvinyl alcohol mixture
WO2022008516A1
Process for manufacture of plasticised homopolymeric polyvinyl alcohol and plasticised polyvinyl alcohol polymer obtained therefrom
WO2022008521A1